Surgical Treatment of the Terrible Triad of the Elbow - Kurinnyi, I.M.; Strafun, O.S. (TERRA ORTHOPAEDICA, 2023)
Summary. The so called “terrible triad” injury of the elbow, which includes a combination of posterolateral dislocation of the forearm with fractures of the radial head and coronoid process, accounts for 10%-11% of all elbow fractures in adults. This type of elbow injury remains difficult to treat and is often accompanied by a high level of complications: instability, contractures, deformable arthrosis, and pain syndrome. Objective: to assess the effectiveness of surgical treatment of patients with the terrible triad of the elbow, depending on the duration of the injury and the features of osteosynthesis of the coronoid process using certain approaches. Material and Methods. The surgical treatment of 87 patients with the terrible triad of the elbow was analyzed. The age of the patients was 40.9±2.6 years. The average term of admission to treatment was 5.5±4.1 months after the injury. 59 patients were admitted in less than 30 days and 28 patients were admitted after 30 days. The preoperative examination included X-ray and CT; sonographic and EMG studies were performed if necessary. Surgical treatment consisted of repositioning and osteosynthesis of the coronoid process, osteosynthesis or prosthetics of the radial head, and restoration of the damaged lateral ligaments of the elbow joint. In cases of consequences of injury, in addition, mobilization of the elbow joint was performed, osteosynthesis was supplemented with bone autograft, and damaged ligaments were restored plastically. After the surgery, the elbow joint was immobilized in the extension position of 30-20 degrees. Postoperative rehabilitation begins on the first day after surgery and involves one cycle of flexion and extension during the day from the extension position of 20-30° to flexion position of 100-120°. Immobilization in the extension position of 20-30° is basic and is used in the evening and at night. Results. The results were evaluated according to the MEPS system in 56±6.2 months. In the group of patients who underwent surgery within 30 days, the MEPS function index was 90.3±2.1 points; when surgery was performed more than 30 days after the injury, statistically worse results were achieved (83.5±2.9 points). We also compared the outcomes of treatment depending on the access to osteosynthesis of the coronoid process. When performing an anterior approach to the coronoid process, the MEPS index was 90.1±3.2 points, which was better than in case of other approaches. Conclusions. Thus, it has been proven that better results in the surgical treatment of the terrible triad are obtained in the group of patients who underwent surgery up to 30 days after the injury compared to later admission to treatment. The advantages of the anterior approach for grade 2-3 coronoid process fractures have been proven. Our proposed early dosed rehabilitation plays an important role in the treatment of such patients.